Preoperative mild cognitive impairment as a risk factor of postoperative cognitive dysfunction in elderly patients undergoing spine surgery - Park, Sujung; Kim, Jeongmin; Ha, Yoon; Kim, Keung N.; Yi, Seong; Koo, Bon-Nyeo (Frontiers in Aging Neuroscience, 2024)
Any persistent degree of cognitive impairment in older adults is a concern as it can progress to dementia. This study aimed to determine the incidence and risk factors for early postoperative cognitive dysfunction (POCD) in elderly patients undergoing spine surgery.Patients were enrolled from a previous prospective observational study after screening for normal cognitive function using the Mini Mental State Examination (MMSE). Cognitive function was evaluated before surgery and at 1 week, month, and year post-surgery using MMSE and Montreal Cognitive Assessment scores(MoCA). Mild cognitive impairment (MCI) was determined using the MoCA scores adjusted for age. POCD was defined as a drop of three or more points on the MMSE 1 week post-surgery. Multivariate logistic analysis was performed to identify POCD risk factors.A total of 427 patients were included. Eighty-five (20%) had pre-existing MCI. The MCI group showed lower MoCA scores at each time point (baseline, 1 week after surgery, 1 month after surgery, 1 year after surgery) compared to the non-MCI group. Those in the MCI group had a higher rate of admission to intensive care unit after surgery, postoperative delirium, and POCD 1 week postsurgery, than those in the non-MCI group (16.5% vs. 6.7%, p = 0.008; 27.1% vs. 15.8%, p = 0.024; and 18.8% vs. 8.2%, p < 0.001, respectively). Among them, 10.3% were assessed for POCD on postoperative day 7 and self-reported poor social roles and physical functioning 1 week postoperatively.Preoperative MCI was seen in ~20% of surgical patients aged > 70 years. POCD was seen in ~20% of patients with pre-existing MCI, and ~10% of those without. Benzodiazepine use, significant comorbidities, pre-existing MCI, and depressive tendencies were risk factors for POCD.